Pelaksanan Vaksinasi Covid-19 Di Kota Makassar - Herlianty, Herlianty; Bahrun, Suriani (Lembaga Penelitian dan Pengabdian Masyarakat,Politeknik Sandi Karsa, 2023)
This pandemic has impacted various social, tourism, and education sectors. It is necessary to intervene not only in terms of health protocols but also other effective interventions are needed through efforts to provide vaccinations; institutions feel the need to carry out community service activities in the form of vaccinations. The purpose of this service is to provide vaccinations to the community. The method used in this activity is counseling about side effects after administering the Covid-19 vaccine and filling out a questionnaire. From the pretest results, it was found that some experienced side effects in the form of drowsiness, fever, chills, and shortness of breath; some did not feel the side effects of administering the vaccine